A review of the structure, function, and application of plant‐based protein–phenolic conjugates and complexes. Issue 2 (15th February 2023) - Yan, Xianghui; Zeng, Zheling; McClements, David Julian; Gong, Xiaofeng; Yu, Ping; Xia, Jiaheng; Gong, Deming
Abstract: Interactions between plant‐based proteins (PP) and phenolic compounds (PC) occur naturally in many food products. Recently, special attention has been paid to the fabrication of PP–PC conjugates or complexes in model systems with a focus on their effects on their structure, functionality, and health benefits. Conjugates are held together by covalent bonds, whereas complexes are held together by noncovalent ones. This review highlights the nature of protein–phenolic interactions involving PP. The interactions of these PC with the PP in model systems are discussed, as well as their impact on the structural, functional, and health‐promoting properties of PP. The PP in conjugates and complexes tend to be more unfolded than in their native state, which often improves their functional attributes. PP–PC conjugates and complexes often exhibit improved in vitro digestibility, antioxidant activity, and potential allergy‐reducing activities. Consequently, they may be used as antioxidant emulsifiers, edible film additives, nanoparticles, and hydrogels in the food industry. However, studies focusing on the application of PP–PC conjugates and complexes in real foods are still scarce. Further research is therefore required to determine the structure–function relationships of PP–PC conjugates and complexes that may influence their application as functional ingredients in the food industry.